2021
DOI: 10.21203/rs.3.rs-1049483/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thinking magically or thinking scientifically: Cognitive and belief predictors of complementary and alternative medicine use in women with and without cancer diagnosis

Abstract: Background Complementary and alternative medicine (CAM) is popular among the general population and patients with various diseases, but our understanding of the predictors of CAM use for the population of women with or without cancer diagnosis is still quite limited. This paper examines predictors of attitudes toward and use of CAM, including cognitive factors (scientific reasoning, health literacy, locus of control), beliefs (holistic and magical health beliefs pseudoscientific beliefs, and trust in doctors)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The early studies explored culturally situated practices from the comparative perspective; in this, they considered their magical components within local contexts, with the explicit or implicit assumption of their inferiority to Western medicine (e.g., Evans-Pritchard, 1976[1937; Rivers, 1924). However, contemporary research has demonstrated that in a globalised world, healing practices coming from different cultural traditions can be combined and transformed into highly syncretic forms; in this, magic becomes part of holistic worldviews linked to spiritual development; and scientific terms are often employed to legitimise magical healing (e.g., Čavojová et al, 2021;Keshet, 2009Keshet, , 2011Koch, 2015;Stevens, 2001). The process of blending traditions is complex and depends on concrete cultural milieus, in which local beliefs and practices can inform new healing systems (e.g., Jerotijević, Hagovská, 2020;Lindquist, 2001Lindquist, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The early studies explored culturally situated practices from the comparative perspective; in this, they considered their magical components within local contexts, with the explicit or implicit assumption of their inferiority to Western medicine (e.g., Evans-Pritchard, 1976[1937; Rivers, 1924). However, contemporary research has demonstrated that in a globalised world, healing practices coming from different cultural traditions can be combined and transformed into highly syncretic forms; in this, magic becomes part of holistic worldviews linked to spiritual development; and scientific terms are often employed to legitimise magical healing (e.g., Čavojová et al, 2021;Keshet, 2009Keshet, , 2011Koch, 2015;Stevens, 2001). The process of blending traditions is complex and depends on concrete cultural milieus, in which local beliefs and practices can inform new healing systems (e.g., Jerotijević, Hagovská, 2020;Lindquist, 2001Lindquist, , 2005.…”
Section: Introductionmentioning
confidence: 99%